Antifungal Mechanism of Dipicolinic Acid and Its Efficacy for the Biocontrol of Pear Valsa Canker - Song, Xue-Ge; Han, Ming-Hui; He, Feng; Wang, Su-Yan; Li, Chao-Hui; Wu, Gui-Chun; Huang, Zi-Gang; Liu, Dong; Liu, Feng-Quan; Laborda, Pedro; Shi, Xin-Chi (Frontiers in Microbiology, 2020)
Valsa pyri is a fatal canker pathogen that causes significant reduction of crop yield in pear orchards. V. pyri invades the trunk phloem, and is difficult to control by chemical treatment. In this work, it was found for the first time that Bacillus subtilis-produced dipicolinic acid (DPA) exhibits antifungal activity against different canker pathogens, including Alteraria alternata, Botryosphaeria dothidea, Rhizoctonia solani and V. pyri. Growth inhibition of V. pyri was observed at less than 5 mM concentration (pH = 5.6). DPA showed the highest antifungal activity at acidic pH values and in the presence of bivalent metals, such as zinc(II), cobalt(II) and copper(II). Measurement of mRNA expression levels and scanning electron microscope (SEM) observations revealed that DPA causes V. pyri apoptosis via inhibition of chitin biosynthesis and subsequent cell lysis. Interestingly, DPA showed high stability in the pear bark and was able to cross the pear tree bark into the phloem, protecting the internal phases of the pear trunk. In preventive applications, DPA reduced the canker symptoms of V. pyri on Cuigan pear trees by 90%. Taken together, an efficient strategy for the management of V. pyri-caused canker disease was developed using a novel antifungal agent, DPA, with strong antifungal activity and particular diffusion properties.